Inhibition of Staphylococcus aureus α-Hemolysin Production Using Nanocurcumin Capped Au@ZnO Nanocomposite - Majid S. Jabir; Taha M. Rashid; Uday M. Nayef; Salim Albukhaty; Faizah A. AlMalki; Jawaher Albaqami; Amal A. AlYamani; Zainab J. Taqi; Ghassan M. Sulaiman (Bioinorganic Chemistry and Applications)
Nanoparticles of gold with zinc oxide (Au@ZnO NPs) were prepared by laser ablation and then capped with curcumin nanoparticles (Cur-Au@ZnO NPs). The synthesized NPs were characterized using different techniques, including transmission electron microscopy (TEM), Fourier-transform infrared spectroscopy (FTIR), UV-visible spectroscopy, and X-ray diffraction. In addition, the ability of NPs as a promising antibacterial agent was tested against Staphylococcus aureus through the agar well diffusion method and AO/EtBr staining assay. The results showed that the prepared nanoparticles (Cur-Au@ZnO) served as an antibacterial agent and can destroy the bacterial cells by losing the cell wall integrity and penetrating the cytoplasmic membrane. Moreover, the findings confirmed the role of the formed NPs in attenuation of the adherence and invasion of S. aureus to rat embryonic fibroblast (REF) cells. Furthermore, the activity of Cur-Au@ZnO NPs against the S. aureus α-hemolysin toxin was evaluated using the western blot technique, using human alveolar epithelial cells (A549), and through histopathology examination in a mouse model. In conclusion, the built Cur-Au@ZnO NPs can be used as a potential antibacterial agent and an inhibitor of α-hemolysin toxin secreted by S. aureus. These NPs may offer a new strategy in combating pathogen infections and in the future for biomedical and pharmaceutical applications.